Contested sustainability discourses in the agrifood system - Constance, Douglas H.; Hatanaka, Maki; Konefal, Jason T.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
The industrial agrifood system is in crisis regarding its negative ecological, economic, and social externalities: it is unsustainable on all dimensions. This book documents and engages competing visions and contested discourses of agrifood sustainability.?.
part PART I Introduction -- chapter 1 Contested sustainability discourses in the agrifood system: an overview / DOUGLAS H. CONSTANCE -- part PART II Framing the contested discourse -- chapter 2 Sustainable intensification: agroecological appropriation or contestation? / LES LEVIDOW -- chapter 3 Sustainable intensification as a sociotechnical imaginary / PAUL B. THOMPSON -- chapter 4 Agrifood discourses and feeding the world: unpacking sustainable intensification / DOUGLAS H. CONSTANCE AND ATHENA MOSELEY -- chapter 5 Sustainability as the civil commons: laying the groundwork for sustainable agriculture / JENNIFER SUMNER -- part PART III Contested discourses in theory and practice -- chapter 6 Zero Hunger discourse: neoliberal, progressive, reformist or radical? / KIAH SMITH -- chapter 7 Greenwashing the animal- industrial complex: sustainable intensification and the Livestock Revolution / LIVIA BOSCARDIN -- chapter 8 Are food quality schemes an alternative to the conventional food system? Reflections on the EU metaphors on agrifood quality regulation / JOSEP ESPLUGA - TRENC, MARINA D I MASSO, -- r DANIEL BORNSTEIN -- chapter 15 Justifying the standardization of sustainability impact / ALLISON MARIE LOCONTO -- part PART V Conclusion -- chapter 16 Fault lines in agricultural sustainability: contestation, cooptation, reform, and transformation / JASON KONEFAL.
Keywords: BUSINESS & ECONOMICS / Industries / General; Agricultural industries; Food industry and trade; Sustainable agriculture